2007
DOI: 10.4171/jems/76
|View full text |Cite
|
Sign up to set email alerts
|

Invariant densities for random $\beta$-expansions

Abstract: Let β > 1 be a non-integer. We consider expansions of the formare generated by means of a Borel map K β defined on {0, 1} N × [0, ⌊β⌋/(β − 1)]. We show existence and uniqueness of an absolutely continuous K β -invariant probability measure w.r.t. mp ⊗ λ, where mp is the Bernoulli measure on {0, 1} N with parameter p (0 < p < 1) and λ is the normalized Lebesgue measure on [0, ⌊β⌋/(β − 1)]. Furthermore, this measure is of the form mp ⊗µ β,p , where µ β,p is equivalent with λ. We establish the fact that the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
91
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 13 publications
0
91
0
Order By: Relevance
“…An interpretation of q-expansions from the perspective of dynamical systems was given in [1], see also [4,5,6]. Let…”
Section: Preliminariesmentioning
confidence: 99%
“…An interpretation of q-expansions from the perspective of dynamical systems was given in [1], see also [4,5,6]. Let…”
Section: Preliminariesmentioning
confidence: 99%
“…One aspect of these representations that makes them interesting is that for α ∈ ( 1 M +1 , 1) a generic x ∈ I α,M has many α-expansions (cf. [4,21,22]). This naturally leads researchers to study the set of x ∈ I α,M with a unique α-expansion, the so called univoque set.…”
Section: Preliminariesmentioning
confidence: 99%
“…In fact it can be shown that Lebesgue almost every t ∈ Γ α − Γ α has a continuum of α-expansions (cf. [4,21,22]). Thus within the parameter space (1/3, 1/2) we are forced to have the following more complicated interpretation of Γ α ∩ (Γ α + t) (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike integer base expansions, for a given β ∈ (1, 2), it is well-known that typically a real number x ∈ I β := [0, 1/(β − 1)] has a continuum of β-expansions with digits set {0, 1} (cf. [2,19]), i.e., for Lebesuge almost every x ∈ I β there exist a continuum of zero-one sequences (x i ) such that x = behaves like a Devil's staircase. Interestingly, for any k = 2, 3, .…”
Section: Introductionmentioning
confidence: 99%